Microencapsulated Garcinia kola and Hunteria umbellata Seeds Aqueous Extracts - Part 2: Influence of Some Selected Pharmaceutical Excipients (International Journal of Phytopharmacy, 2016)
Objective: This study investigates the effect of selected excipients on microcapsules properties of seeds extracts of Garcinia kola (GK) and Hunteria umbellata (HU). Method: Extracts from macerated dried powdered seeds were microencapsulated with chitosan-alginate including either talc, HPMCAS, EudragitRLPO or EudragitL100 up to 25% in the core. Microcapsules were characterized using differential scanning calorimertry (DSC), X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FTIR) and In vitro release. Results: DSC, XRD and FTIR showed no change in crystalline properties and functional groups of microcapsules and excipients in the formulations. In vitro extract release showed retardation of extract release in acid medium after 2 h and between 80 to 100% at pH 6.8. Generally, the microcapsules fitted more closely to first order model than the other models. Conclusion: Inclusion of these excipients did not impart negatively in interaction and release profile on microcapsules containing GK and HU aqueous extracts and can therefore be added to facilitate microcapsule production and enhance dosage form performance.